Eat the cookie-- buy the shoes [compact disc, unabridged] : giving yourself permission to lighten up - Meyer, Joyce, 1943- (Hatchette Audio, 2010)
The author argues that breaking from a regimented lifestyle is not a sign of weakness, but rather a sign that balance is a core value in life.